DAMPAK KETERBUKAAN PERDAGANGAN, FDI, DAN PERTUMBUHAN EKONOMI TERHADAP STABILITAS MONETER MELALUI NILAI TUKAR EFEKTIF RIIL DI INDONESIA - A. Rahmat Adi; Kamal Fachrurrozi; Nur Aidar (Syiah Kuala University, 2022)
AbstractThere are still few studies on Indonesia's Effective Real Exchange Rate, so this study tries to examine the determination of Indonesia's Effective Real Exchange Rate (REER). The variables used in this study are Trade Opponess, Foreign Direct Investment (FDI), and Gross Domestic Product (GDP) with time series data from 1990-2019. Data obtained from The Federal Reserve (The Fred) and the World Bank. The analytical method used in this research is Autoregressive Distributed Lag (ARDL). The results show that trade opennes has a negative effect on REER, while FDI both in the short and long term has a positive effect on REER, but GDP has a positive effect in the short term but does not have a significant effect in the long term on REER. Based on these findings, the government needs to pay serious attention to REER by maintaining exchange rate stability.